Metatranscriptome analysis of the reef-building coral Orbicella faveolata indicates holobiont response to coral disease - Daniels, Camille; Baumgarten, Sebastian; Yum, Lauren K.; MIchell, Craig T.; Bayer, Till; Arif, Chatchanit; Roder, Cornelia; Weil, Ernesto; Voolstra, Christian R. (Frontiers in Marine Science, 2015)
White Plague Disease (WPD) is implicated in coral reef decline in the Caribbean and is characterized by microbial community shifts in coral mucus and tissue. Studies thus far have focused on assessing microbial communities or the identification of specific pathogens, yet few have addressed holobiont response across metaorganism compartments in coral disease. Here, we report on the first metatranscriptomic assessment of the coral host, algal symbiont, and microbial compartment in order to survey holobiont structure and function in healthy and diseased samples from Orbicella faveolata collected at reef sites off Puerto Rico. Our data indicate metaorganism-wide as well as compartment-specific responses to WPD. Gene expression changes in the diseased coral host involved proteins playing a role in innate immunity, cytoskeletal integrity, cell adhesion, oxidative stress, chemical defense, and retroelements. In contrast, the algal symbiont showed comparatively few expression changes, but of large magnitude, of genes related to stress, photosynthesis, and metal transport. Concordant with the coral host response, the bacterial compartment showed increased abundance of heat shock proteins, genes related to oxidative stress, DNA repair, and potential retroelement activity. Importantly, analysis of the expressed bacterial gene functions establishes the participation of multiple bacterial families in WPD pathogenesis and also suggests a possible involvement of viruses and/or phages in structuring the bacterial assemblage. In this study, we implement an experimental approach to partition the coral holobiont and resolve compartment- and taxa-specific responses in order to understand metaorganism function in coral disease.